IMPLEMENTASI PENDIDIKAN KARAKTER SISWA MELALUI KEGIATAN USROH DI SMP PEMBANGUNAN LABORATORIUM UNP PADANG - Efendi Efendi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2019)
AbstractThe purpose of this study is to describe the application of the values of Character Education Through Usroh Activities. Character education is an education system that instills values in each individual, which includes knowledge, awareness and actions to be able to apply praiseworthy behavior to the almighty God, towards oneself, others, the environment and the nation and country. This type of research is field research that uses a qualitative approach. Collecting data in this study using interviews, observation and documentation. While the data analysis method uses descriptive analysis. The results of the discussion showed that the application of character education in SMP UNP Padang Laboratory Development included several activities including reading Asmaul Husna, reading the Koran, advice from the school principal, reading the Al-Fatihan letter for parents, praying for students, teachers, and people old and finally closed with remembrance. The activity was carried out before the teaching and learning activities in the school yard. This activity is carried out every Tuesday to Friday. The values of character education that are expected to be embedded from these activities include, among others, religious, disciplined, responsible and creative.